Whistleblowing System Sebagai Pilar Integritas: Upaya Pencegahan Kecurangan Dan Penguatan Good Corporate Governance Dalam Perspektif Al-Qur’an Dan Hadis - Divia Permatasari; Edtiyarsih, Denari Dhahana (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2026)
The presence of (GCG) has been identified as a significant contributing factor that facilitates the occurrence of fraudulent activities. One such mechanism that has gained recognition for its efficacy in detecting and preventing fraud is the whistleblowing system (WBS). However, its implementation continues to encounter various challenges. The objective of this study is to identify the impediments to the implementation of WBS, to analyze optimization measures, and to examine its contribution to supporting GCG principles from the perspective of the Qur'an and Hadith. The present study employs a qualitative methodology, underpinned by a comprehensive literature review, to explore the tenets of WBS and GCG through an Islamic lens. The data collection techniques employed in this study entailed a meticulous review of extant literature, encompassing both primary and secondary sources, including books, journals, and articles. The analysis of data was conducted through the implementation of content analysis and synthesis analysis, with the objective of interpreting the meaning of various literature sources that are related to the subject. The findings indicated that the implementation of WBS is frequently impeded by a paucity of managerial support, inadequate safeguards for whistleblowers, and a reporting system characterized by insecurity. Additional challenges include an organizational culture that is not conducive to innovation and lax regulatory oversight. The optimization of WBS can be achieved through strategic measures, including the establishment of a supportive reporting environment, the provision of anonymous complaint channels, the delivery of training, and the conduction of periodic audits and evaluations. A robust implementation of WBS has the potential to reinforce the tenets of GCG, particularly transparency, accountability, independence, responsibility, and fairness.